Biomaterials. Approved and developing materials for medical use - Lytkina, Darya N.; Pajaziti, Betina; Heinrich, Lothar A.; Kurzina, Irina A. (TSU Press, 2023)
The book encompasses vital insights into the field of biomaterials science, delving into the utilization of synthetic materials as medical implants across diverse clinical applications. It provides comprehensive details, covering the classification, certification prerequisites, aspects of biocompatibility, interactions with the physiological system, and considerations regarding risks and microbial contamination. Information about metal-ceramic, polymer, composite and non-metallic materials used in medical practice is presented. The book is recommended as an education book for bachelors, masters and graduate students of universities, for teachers and researchers working in the field of biomaterials science.